Still hand in glove? A re-examination of state-funded activism - Christopher Snowdon (Institute of Economic Affairs (IEA), 2019)
This discussion paper revisits the issue of state-funded activism in the UK and EU. It starts with the hypothesis that there has been a decline in taxpayers' money given to political advocacy groups because (1) budget cuts under 'austerity' have made less money available to non-governmental bodies, (2) new grant standards introduced in 2016 explicitly forbid grant funds being used for advocacy, lobbying, and campaigning. Evidence from the charity sector suggests that overt campaigning with money from central government has declined. Several of the organisations mentioned in the previous reports are no longer in receipt of departmental grants. A few have closed. Others have successfully ,diversified their funding base. International development charities have tended to see their statutory funding increase, but there is no evidence that the money is used for political advocacy. State-funded activism continues to be endemic at the EU level. Most of the organisations mentioned in the IEA's 2013 report Euro Puppets receive more money from EU bodies than they did in 2011 and most of them rely on the EU for the majority of their income. In the environmental field, most of the big 'green' NGOs have seen their EU funding increase and a multitude of likeminded groups receive grants from a exteuro20 million EU programme. In the 'nanny state' field, statutory funding of pressure groups remains common in the EU and the devolved governments of the UK. The picture is mixed in local government with some groups being dissolved while others are formed. In England, funding has tended to move away from overt pressure groups and towards activist-academics and umbrella groups. The critical new dynamic has been the creation of Public Health England, a quango which acts as a funder of activist groups and an advocacy organisation in its own right. Activist groups appear to be receiving less money from Whitehall than they did five years ago. It is difficult to ascertain whether this is because of budget cuts or because of the new grant standards. Whatever the reason, the use of public money to oppose the free market has become less blatant in England while remaining common in Scotland, Wales and the EU
Keywords: L51; L31; L32; L38; L51; L31; L32; L38; 330